YouTube Music as an Innovative Teaching Media to Improve Students’ Listening Mastery - Izza Amalia Rahman; Mutmainnah Mustofa; Izzatin Nisa' (Jurnal Paedagogy, 2022)
This research aims to investigate the effectiveness of YouTube Music platform as teaching media to improve students’ listening mastery. It is believed that YouTube Music as an innovative media could be used effectively to attract students’ interest in increasing their listening mastery. By using true-experimental research with quantitative design, there are 52 students were divided into two groups, 26 students for experimental group and 26 students included in control group. This research used test and questionnaire as research instrument. There are several findings to prove that YouTube Music platform is an effective media to improve students’ listening skills. By conducting test as first instrument, it was found that the average score of students taught by YouTube music was 79.85. It was higher than those who taught by conventional media (71.50). By analyzing the data, it can be concluded that there are significant different between students taught by innovative media than those taught by conventional media. This result also affected by students’ perception in learning listening which was found by students’ answer from questionnaire.